Pengaruh Karakteristik Individu terhadap Fungsi Paru pada Petugas Penyapu Jalanan - Hansen, Hansen; Utama, Deddy Alif (Poltekkes Kemenkes Tanjung Karang, 2021)
The increase in the number of vehicles in Samarinda City occurs significantly every year this has the potential to decrease environmental quality, namely air pollution. People who are at risk of air pollution are street sweepers who work on the streets every day so that it can have an impact on health. Therefore, the purpose of this study was to determine the individual characteristics of lung function among street sweeping officers in Samarinda City. This research is a type of observational analytic study with a cross-sectional research design that has the aim of analyzing the risks to the consequences that are caused together. This research is included in the quantitative description. The research location was carried out along the protocol road in Samarinda City. The study population was street sweeping officers who were taken randomly amounting to 55 people. This study consisted of the dependent variable, namely lung function, and the independent variables were gender and year of service. Data analysis her use fisher’s exact. Data were collected using questionnaires and interviews, measuring lung function on street sweeping officers using a spirometer, while interviews were carried out to determine the sex and year of service of the officers while working as a street sweeper in Samarinda City. The results of the bivariate analysis of individual characteristics, namely between gender and lung function obtained p-value=0,674, while the bivariate results between a work period and lung function obtained p-value 0,219. There was no significant relationship between gender, work period, and lung function.